Reality and Hyperreality Behind the Kidfluencer Phenomenon - Irawati Diah Astuti (Universitas Multimedia Nusantara, 2022)
Apart from being a medium of communication, social media is also a place for some people to earn money. Not only adults, but children are also present on social media as objects to make money by becoming kidfluencers or child influencers. This becomes a controversy because social media platforms limit their users by age rules to avoid various dangers and negative impacts lurking that will create impact on children in the future. However, parents and relatives of the kidfluencers choose to neglect and continue breaking the rules on social media so their children could be kifdluencers. This study aims to examine the phenomenon of kidfluencers and their relation to the hyperreality theory by Jean Baudrillard. By becoming kidfluencers, these children are displayed in such a way on social media complete with their cuteness on daily basis that eventually invite various responses from their followers and influence them in most of the things they do. Yet, the actual reality does not always match what is present on social media. With a qualitative method, this phenomenon is then investigated to find out that what the kidfluencers show is not the actual reality, but only a representation that refers to themselves, not to others.